THE EFFECT OF DIGITAL MARKETING THROUGH GEN Z VOTING DECISION IN 2024 ELECTION - Listia Nurjanah; Fernando Tandrian (Journal of Global Business and Management Review, 2026)
This study investigates how digital marketing influences the political preferences and engagement of Gen Z voters in Batam City, utilizing Trust as a mediating factor. Employing a quantitative methodology, the research analyzed 304 Gen Z participants selected via purposive sampling using Smart PLS software. The framework evaluates variables such as Social Media Marketing, Influencer Marketing, Advertising, Trust, and the final Voting Decision. The results demonstrate that digital marketing channels significantly bolster Trust, which subsequently drives voting behavior. Furthermore, Trust acts as a vital bridge between online promotional efforts and political choices, suggesting that candidates must prioritize building digital credibility to successfully convert online engagement into offline votes.